Epidemiological statistics of congenital thumb duplication in the Chinese population - Yao, Yingling; Zhou, Haolin; Li, Lianyong; Nan, Guoxin (Journal of orthopaedic surgery and research, 2021)
Thumb duplication is a very common congenital malformation. This study describes and compares the phenotypic manifestations of polydactyly between southwest and northeast China. However, previous studies had a limited sample size. Therefore, this study used a large sample. A total of 3549 well-characterized thumb duplication cases were divided into group A (southwest China) and group B (northeast China). In group A and group B, the left-to-right ratio was 1:1.5 and 1:1.75, respectively, and the female-to-male ratio was 1:1.5 and 1:1.58, respectively. There were no significant differences in gender distribution or the distribution of left and right polydactyly between the two groups, but the distribution of bilateral polydactyly was significantly different.